The Global Financial Crisis: An Update on the Effects on Bolivia - Luis Carlos Jemio; Osvaldo Nina (Institute for Advanced Development Studies (INESAD), 2009)
The global financial crisis (GFC) has had a negative effect on the Bolivian economy. The outbreak of the GFC has caused a drop in export commodity prices such as mining and hydrocarbons, and a reduction in remittances. Bolivia however, was in a relatively good position to deal with the negative effects of the GFC. The country has experienced in recent years an important commodity price boom, which significantly increased external revenues, public and private incomes and consumption levels. Although the GFC has had a mild effect on the Bolivian economy so far, there are important structural factors that could put at risk the long term sustainability of policies and of the macroeconomic equilibriums. Among these factors are: i) a low investment rates, which could risk growth prospects and employment creation; ii) a large dependency of Bolivia fiscal sector on the hydrocarbon rent, which makes the long term sustainability of macroeconomic policies and of the current economic situation questionable; iii) the lack of a favourable investment climate required to increase growth and employment, which depends among other factors of the rule of law, property rights, judicial security, clearer and more stable rules of the game, macroeconomic stability, etc. iv) lack of a clearer strategy in relation to the country external insertion is also necessary. Access to larger markets, with higher incomes and purchasing power, is necessary to promote sustainable growth and employment creation, and to reduce the vulnerability of the Bolivian economy to shocks. Trade agreements with the USA, European Union and other regions of the world are necessary to promote investment, growth and employment creation.
Keywords: G01; 330; Financial crisis; Bolivia